Energetics of activation in frog and toad muscle - Smith, I. C. H. (1972)
1. If activation heat reflects the operation of the calcium pump it should be independent of actomyosin activity. The semitendinosus preparation affords a technique for removing actomyosin activity since the muscle can be stretched till there is almost no overlap between the filaments. 2. Heat production, H, in twitches and tetani of stretched muscle fits the relation H = A+M.P/P(ot) where P/P(ot) is the fraction of the optimal tension remaining at the stretched length and A and M are assumed to be the activation dependent and actomyosin dependent heat components. 3. For twitches the A component is early and fast and constitutes 0·26 (S.D. 0·09) of the heat production at normal muscle lengths. Its time course is similar in both frog and toad muscle although both M and P are twofold slower in toad muscle. High concentrations of CO(2) slow only M and P(ot). The A component is associated with a normal recovery heat. 4. The twitch-tetanus tension ratio, after correction for the extra shortening that occurs during a tetanus, does not vary with the degree of muscle stretch: it is thus probable that twitch activation does not vary with muscle stretch. 5. Moderately hypertonic Ringer solution reduces M and P(ot) but not A, but strongly hypertonic solution also reduces A. Zn(2+), No(3)(-) and second shock potentiation of a twitch increase A, M and P(ot) in proportion to each other.